BnText2Table – dataset and Text-to-Table generation in Bangla - Zariyat, Tahreema Rahman; Ahmed, Fahim Irfan; Oishi, Tahsina Tajrim; Morshed, Maruf (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.